Photoacoustic technology for biological tissues characterization - Hui Ling Chua; Audrey Huong (Bulletin of Electrical Engineering and Informatics, 2020)
The existing photoacoustics (PA) imaging systems showed mixed performance in imaging characteristic and signal-to-noise ratio (SNR). This work presents the use of an in-house assembled PA system using a modulating laser beam of wavelength 633 nm for two-dimensional (2D) characterization of biological tissues. The differentiation of the tissues in this work is based on differences in their light absorption, wherein the produced photoacoustic signal detected by a transducer was translated into phase value that corresponds to the peak amplitude of optical absorption of tissue namely fat, liver and muscle. This work found fat tissue to produce the strongest PA signal with mean ± standard deviation (SD) phase value = 2.09 ± 0.31 while muscle produced the least signal with phase value = 1.03 ± 0.17. This work discovered the presence of stripes pattern in the reconstructed images of fat and muscle resulted from their structural properties. In addition, a comparison is made in an attempt to better assess the performance of the developed system with the related ones. This work concluded that the developed system may use as an alternative, noninvasive and label-free visualization method for characterization of biological tissues in the future.